New Insights Into Structure and Function of TIFY Genes in Zea mays and Solanum lycopersicum: A Genome-Wide Comprehensive Analysis - Heidari, Parviz; Faraji, Sahar; Ahmadizadeh, Mostafa; Ahmar, Sunny; Mora-Poblete, Freddy (Frontiers in Genetics, 2021)
The TIFY gene family, a key plant-specific transcription factor (TF) family, is involved in diverse biological processes including plant defense and growth regulation. Despite TIFY proteins being reported in some plant species, a genome-wide comparative and comprehensive analysis of TIFY genes in plant species can reveal more details. In the current study, the members of the TIFY gene family were significantly increased by the identification of 18 and six new members using maize and tomato reference genomes, respectively. Thus, a genome-wide comparative analysis of the TIFY gene family between 48 tomato (Solanum lycopersicum, a dicot plant) genes and 26 maize (Zea mays, a monocot plant) genes was performed in terms of sequence structure, phylogenetics, expression, regulatory systems, and protein interaction. The identified TIFYs were clustered into four subfamilies, namely, TIFY-S, JAZ, ZML, and PPD. The PPD subfamily was only detected in tomato. Within the context of the biological process, TIFY family genes in both studied plant species are predicted to be involved in various important processes, such as reproduction, metabolic processes, responses to stresses, and cell signaling. The Ka/Ks ratios of the duplicated paralogous gene pairs indicate that all of the duplicated pairs in the TIFY gene family of tomato have been influenced by an intense purifying selection, whereas in the maize genome, there are three duplicated blocks containing Ka/Ks > 1, which are implicated in evolution with positive selection. The amino acid residues present in the active site pocket of TIFY proteins partially differ in each subfamily, although the Mg or Ca ions exist heterogeneously in the centers of the active sites of all the predicted TIFY protein models. Based on the expression profiles of TIFY genes in both plant species, JAZ subfamily proteins are more associated with the response to abiotic and biotic stresses than other subfamilies. In conclusion, globally scrutinizing and comparing the maize and tomato TIFY genes showed that TIFY genes play a critical role in cell reproduction, plant growth, and responses to stress conditions, and the conserved regulatory mechanisms may control their expression.